If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3k-14=(k-5)=1
We move all terms to the left:
3k-14-((k-5))=0
We calculate terms in parentheses: -((k-5)), so:We get rid of parentheses
(k-5)
We get rid of parentheses
k-5
Back to the equation:
-(k-5)
3k-k+5-14=0
We add all the numbers together, and all the variables
2k-9=0
We move all terms containing k to the left, all other terms to the right
2k=9
k=9/2
k=4+1/2
| 64-3x=73 | | 4t−8=4t−8= 3636 | | 3/x=49 | | 4t−8=4t−8= 36 | | X2+4x-9=4 | | (17^x)^3=17 | | d+10.0=92 | | |2-6x|=38 | | 2x=(4-2) | | g+2/3=1/4 | | 34(x)=447 | | x÷1.4=2.7 | | -1=0.5*x(9) | | 34x=447 | | 125r=500 | | g-16=11 | | .-8+x=24 | | -1=0.5*x9 | | -56÷-4+19=x | | -8(g+2=-16-8g | | q÷3/7=7/10 | | q÷37=710 | | 30/(7n)=1 | | 4g=-7 | | n+(n+2)*3=(n+4)*14-58 | | 15x+1-7x-3=180 | | .10(28-q)+.25q=4.30 | | 2n-6+6n+5=-9 | | 10y+7−4y=–10y+7 | | 4e-10=2e+8 | | 1/2x-1/4=1/4 | | 176/pp=2 |